ANALISIS GAYA BELAJAR MURID KELAS IV DI SDN BETTE KABUPATEN BARRU - SRI WAHYUNI, SRI WAHYUNI; M. Basri; Muh. Nawir (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2020)
This study aimed to describe the style of learning, supporting factors and factors inhibiting the learning styles of fourth-grade students at SDN Bette Barru. The subjects of this study are the fourth-grade students at SDN Bette Barru. This research is a descriptive qualitative approach. The data collection is carried out through observation, interview and document study. The data analysis technique is done with the collection, reduction, display, and conclude. Researchers used the test of credibility, dependability, and confirmability to obtain the validity of the data. The results showed that fourth-grade students learning styles vary. This is evidenced by the results of the analysis of learning styles of students showed that of the six pupils who are subject to two research students have a tendency of learning styles auditory, two research students have a tendency of learning styles visual, and two research students have a tendency of learning styles kinesthetic. Factors supporting this research is the availability of adequate facilities so that the teacher can use a variety of teaching methods in the learning process, as well as a limiting factor in this study is not maximal teachers in using existing facilities at the school.